2018
DOI: 10.1097/lgt.0000000000000422
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer Screening Among Women by Birthplace and Percent of Lifetime Living in the United States

Abstract: These findings may inform cervical cancer screening efforts targeting foreign-born women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 23 publications
(25 reference statements)
0
19
0
Order By: Relevance
“…[4][5][6]15,16 The results from this study suggest that older foreign-born women who stop screening at age 65 years may not have been adequately screened previously. Work by Endeshaw et al 17 further supports this conclusion, finding that 17.1% of foreign-born women older than age 65 years have never been screened for cervical cancer, compared with 6.0% of U.S.-born women older than age 65 years.…”
Section: Discussionmentioning
confidence: 86%
“…[4][5][6]15,16 The results from this study suggest that older foreign-born women who stop screening at age 65 years may not have been adequately screened previously. Work by Endeshaw et al 17 further supports this conclusion, finding that 17.1% of foreign-born women older than age 65 years have never been screened for cervical cancer, compared with 6.0% of U.S.-born women older than age 65 years.…”
Section: Discussionmentioning
confidence: 86%
“…However, we have the possibility of reaching the highest-risk women if we make self-sampling a priority for screening populations that are not accessing clinician-based screening for cervical cancer. A recent publication by Endeshaw et al 26 found that foreign-born women have limited access to screening—between 10 and 28% of those women had never received a Pap smear. Dr. Pierce very accurately mentioned the challenges associated with reaching unscreened women and motivating them to collect and return a self-collected sample.…”
Section: Discussionmentioning
confidence: 99%
“…[35] The low uptake of screening observed in our study are similar to findings from other studies reporting lower screening proportions among refugees and immigrants when compared to U. S. born populations. [19][20][21]36] Acceptance of screening was highest among the Myanmar and Bhutanese groups. The Building Bridges program was most effective in these two culture groups.…”
Section: Plos Onementioning
confidence: 99%